2022
DOI: 10.1039/d1cc05924f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a two-dimensional DNA–RNA hybridized membrane for collecting tumor-derived exosomes

Abstract: Macroscopic nucleic acid‒based structures have attracted much attention in biomedical fields. Here, we introduce a novel DNA-RNA hybridized membrane structure via enzymatic dual polymerization. The membrane exhibited enhanced rigidity and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Among these sources, nucleic acids, as biomacromolecule, have garnered significant attention as potential candidate to fulfill the desired properties of the ideal Bioplastic, including on-demand degradability for ideal bioplastics. In this regard, nucleic acid, which is found to be universally present in all organisms and present throughout ecosystems, offers substantial potential as an abundant plastic resource derived from biomass . Previous studies have demonstrated the versatility of nucleic acids as biomolecular building blocks for constructing macroscale structures through various approaches. Notably, attempts to create DNA-based cross-linked structures have employed methods such as DNA branching, metal doping, and enzymatic amplification . However, achieving the desired level of mechanical properties for practical applications remains a challenge, as these structures typically exhibit low storage–loss modulus in the range of a few thousand to hundreds of pascals and are limited in manufacturing capabilities, primarily restricted to molding processes.…”
mentioning
confidence: 99%
“…Among these sources, nucleic acids, as biomacromolecule, have garnered significant attention as potential candidate to fulfill the desired properties of the ideal Bioplastic, including on-demand degradability for ideal bioplastics. In this regard, nucleic acid, which is found to be universally present in all organisms and present throughout ecosystems, offers substantial potential as an abundant plastic resource derived from biomass . Previous studies have demonstrated the versatility of nucleic acids as biomolecular building blocks for constructing macroscale structures through various approaches. Notably, attempts to create DNA-based cross-linked structures have employed methods such as DNA branching, metal doping, and enzymatic amplification . However, achieving the desired level of mechanical properties for practical applications remains a challenge, as these structures typically exhibit low storage–loss modulus in the range of a few thousand to hundreds of pascals and are limited in manufacturing capabilities, primarily restricted to molding processes.…”
mentioning
confidence: 99%